2009
DOI: 10.2460/ajvr.70.12.1545
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum iohexol clearance and plasma creatinine clearance in clinically normal horses

Abstract: Objective-To determine whether a limited sampling time method based on serum iohexol clearance (Cl(iohexol)) would yield estimates of glomerular filtration rate (GFR) in clinically normal horses similar to those for plasma creatinine clearance (Cl(creatinine)). Animals-10 clinically normal adult horses. Procedures-A bolus of iohexol (150 mg/kg) was administered IV, and serum samples were obtained 5, 20, 40, 60, 120, 240, and 360 minutes after injection. Urinary clearance of exogenous creatinine was measured du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
4
19
0
Order By: Relevance
“…Plasma clearance of IOX was recently used to evaluate GFR both in adult horses and foals. Wilson et al [29] reported a GFR of 2.38 mL/kg/min in adult horses, whereas Gonda et al [28] obtained a GFR of 2.15 mL/kg/min in foals. Our results obtained in horses with the nine-point method are in line with literature.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Plasma clearance of IOX was recently used to evaluate GFR both in adult horses and foals. Wilson et al [29] reported a GFR of 2.38 mL/kg/min in adult horses, whereas Gonda et al [28] obtained a GFR of 2.15 mL/kg/min in foals. Our results obtained in horses with the nine-point method are in line with literature.…”
Section: Discussionmentioning
confidence: 97%
“…To the authors' knowledge, literature regarding the use of IOX to evaluate GFR in the horse is scarce [28,29], and no data are reported in donkeys. The aims of this study were (1) to estimate GFR using IOX clearance in horses and donkeys and (2) to evaluate the use of limited sampling models to establish an accurate and clinically suitable GFR test.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The dose of 20 mg I/kg iodixanol corresponded to about one-twenty-sixth the human clinical dose as the contrast medium for angiography, and about one-seventh the iohexol dose (150 mg I/kg) described in the previous report (Wilson et al 2009). The three-blood-sample method is considered to have many practical advantages such as repeated application to the same animals, usage of non-radiolabeled agent and a small amount of serum specimen (80 μL), compared to the previously reported methods in horses (Brewer et al 1988;Gleadhill et al 1999;Matthews et al 1992;Walsh and Royal 1992;Wilson et al 2009;Zatzman et al 1982). However, since species differences in the formula of Bröchner-Mortensen (1972) have not been systematically evaluated, further studies are required to collect cumulative background data including increased number of horses together with clinical cases showing reduced renal function.…”
Section: Resultsmentioning
confidence: 97%
“…Renal dysfunction in horses may develop secondary to changes in hemodynamics (Gleadhill et al 2000), intrinsic renal diseases, or postrenal diseases (Wilson et al 2009). However, there is no information dealing with a simple prediction of equine GFR.…”
Section: Introductionmentioning
confidence: 99%